Clinical and Imaging Features of a Congenital Midline Cervical Cleft in a Neonate: A Rare Anomaly - Rachelle Goldfisher; Pritish Bawa; Zachary Ibrahim; John Amodio (Case Reports in Pediatrics)
Congenital midline cervical cleft (CMCC) is a rare congenital anomaly. CMCC and its complications and treatment have been well described in ENT, dermatology, and pediatric surgery literature. However, to our knowledge, the imaging work-up has not been reported in the literature thus far. We present a case of CMCC in a neonate with description of clinical presentation and imaging features.